REDUCTION OF STUDENT MISCONCEPTIONS: APPLICATION OF TTW-PBL LEARNING WITH CHEMICAL REPRESENTATION ON BUFFER SOLUTION MATERIALS - Latika Ulfah; Muhammad Kusasi; Almubarak Almubarak (JURNAL PENA SAINS, 2021)
The research was conducted on the chemical representation of buffer solution learning through multi-model TTW-PBL learning to determine the understanding of chemical representation and reduce students' misconceptions. The method used is a quasi-experimental design with a non-equivalent control group. The samples of this study were students of class XI MIPA 1 as the experimental class and XI MIPA 3 as the control class at SMAN 11 Banjarmasin. The independent variables are the TTW-PBL learning model in chemical representation and the PBL model in chemical representation. In contrast, the dependent variable is the understanding of chemical representations and misconceptions. The data analysis technique used descriptive and inferential analysis techniques. Descriptive analysis was used to find out the differences in students' misconceptions. The inferential analysis uses a t-test to analyze differences in understanding of chemical representations. The results showed significant differences in the understanding of chemical representation in the class using the multi-model TTW-PBL and PBL model with a value of tcount ttable = 2.15 1.99 and the percentage of misconceptions of 16.57% and 23.24%, respectively. Finally, TTW-PBL learning with Chemical Representation can reduce students misconception.